Meetings Across the Paradigmatic Divide - Moss, Peter (Educational philosophy and theory, 2007)
The problematique addressed by the article is the growth of a dominant discourse in early childhood education and care, which has a strong effect on policy and practice, paralleled by an increasing number of other discourses which problematise most of the values, assumptions and understandings of the former. Yet there is very little engagement between these discourses, in large part because they are situated within different paradigms-modernity in the former case, postfoundationalism in the latter. The author argues that the absence of dialogue and debate impoverishes early childhood and weakens democratic practice. The article considers whether and in what conditions the concept of agonistic pluralism might provide a framework for political engagement among at least some on either side of the paradigmatic divide, and takes evaluation as one example of a subject for an agonistic politics of early childhood.